All You Need to Know About Making Memory Albums - Wright, Maggie, 1947- (Tunbridge Wells, Kent, Eng. Search Press, 1998)
Let Maggie Wright help to create a beautiful illustrated memory album. She shows how to turn photographs into unique keepsakes that can be treasured for years to come. Contains over 70 step-by-step photographs and many innovative ideas for decorating each page. 122 color illustrations
Include Color Illustration and Index
Keywords: Photograph albums -- Photographs--Conservation and restoration -- Scrapbooks